(untitled) (Italian Journal of Public Health, 2008)
Background: The European Community recommends mammography, cervical and colorectal cancer screening programmes. In Italy, cancer screening programmes have been included in the Basic Healthcare Parameters (Livelli Essenziali di Assistenza) since 2001. Full national coverage of a population-based organized screening programme has been planned for in Italy and is being implemented. Since 2005, the Ministry of Health - Department of Prevention has formally charged The National Centre for Screening Monitoring (Osservatorio Nazionale Screening –ONS-) with monitoring and promoting screening programmes nationwide. Participation of target populations is a key indicator of the impact and efficacy of a screening programme in reducing cancer mortality. Methods: Attendance of invitees is one of the indicators calculated every year in the quality control of Italian screening programmes. Data collection is organized by means of a structured questionnaire, sent by ONS to the referent for data collection in each Region, who then returns the completed questionnaires to the Regional Centre. Questionnaires are then sent to the National Centre. Logical and epidemiologic checks are performed at both levels. Every year ONS publishes reports on the results of the surveys. A feasibility study for a National data warehouse based on individual records is in progress. The national survey “Multiscopo sulle famiglie” and the Passi Study (Progetti delle Aziende Sanitarie per la Salute in Italia) provided additional information regarding spontaneous preventive health care activities in the Italian population. Results: Mammography screening: In 2006, 78.2% of Italian women aged 50-69 lived in areas where organised screening was in place (theoretical extension), however, the distribution of the screening activity is not uniform (higher in Northern/Central Italy compared with Southern/Insular Italy). Similar geographical distributions can be noted in the attendance rates (60.5% in the North of Italy, 56% in the Central area and 38.3% in the South of Italy). Cervical cancer screening: From the data obtained by the 2006 survey, 93.5% of theoretical extension was registered in the Centre of Italy, 65% in the North and 65.5% or in the South of Italy. 38.5% of invited women underwent a Pap-test. A decreasing trend in participation can be observed from Northern (45.6%) to Central (35.7%), and to Southern (28.7%) Italy. Colorectal cancer screening: In 2006, theoretical extension of colorectal cancer screening in Italy was 44%, with significant differences in geographical distribution (66.1% in the North of Italy 48.5% in the Centre and about 10% in the South of our country). About 907,000 people had a faecal occult blood test in 2006 (adjusted compliance of 44.6%). Data from the survey “Multiscopo sulle famiglie” showed that organised screening activity can reduce social inequalities of access to cancer screening, increasing screening utilization particularly in less educated people. Conclusions: Organised cancer screening programmes have been extended in recent years, improving the equity in the access to early diagnosis for the people invited. However, social and geographical inequalities still remain.